Minimum Design : Alessandro Mendini - Ciagà, Graziella Leyla (24 ORE Cultura, 2011)
Alessandro Mendini, born in Milan in 1931, is a major theorist and a driving force behind avant-garde design in Italy. Aside from his artistic career, he was also editor of the architecture magazines Casabella and Modo and publisher of the famous 'Domus' magazine. Considered to be one of the most important contemporary designers in Europe, Mendini's work places an emphasis on cultural diversity and radical expression. He has also produced many collective projects, such as the museum in Groningen, Netherlands, built with Philippe Starck, Frank Stella, and Michele de Lucchi. He has also worked with important Italian and foreign firms as Zanotta, Alessi, Swatch, Philips, Venini, Bisazza and Cartier.
Serie Minimum Design o.l.v Andrea Branzi
Engels
boek
Keywords: Mendini, Alessandro; Italië